(untitled) (Annals of Medical Research, 2022)
Aim: The objective of this study is to assess the choice of first-line and other line options, treatment outcome, and survival effects in transplant-ineligible patients with multiple myeloma (MM) in the novel anti-myeloma agents’ era. Materials and Methods: Forty-five transplant-ineligible patients with MM were evaluated retrospectively. Patients’ characteristics, disease score, cytogenetic, LDH, treatment lines, treatment protocol, treatment response, and survival status at the last follow-up were examined. Results: The median age was 71 (range, 60-85) years. Thirty-nine (86.6%) patients were over 65 years old, 32 (71.1%) of them had poor performance scores and 25 (55.6%) of them had comorbidity. The most used induction regimen was bortezomib plus cyclophosphamide plus dexamethasone (n:33;73,3%). The overall response rate was detected in 30 (66,6%) patients in overall induction regimens. The maintenance treatment was applied to 14 (31,1%) patients after induction treatment and lenalidomide plus dexamethasone (Rd) was used for maintenance treatment. Twelve (85,8%) patients are still on maintenance treatment with VGPR or better response. The most used second-line regimen was Rd (n:12; 46,1%) and bortezomib plus lenalidomide plus dexamethasone (n:9;34,6%). The median follow-up period was evaluated as 36 (1-81) months. After the first-line treatment, progression-free survival was found to be 12 (0-64) months. The median overall survival (OS) was 17 (1-81) months. Twelve patients are alive without progression. The median OS was significantly shorter among patients with high LDH at the time of diagnosis than patients with normal LDH [28 (12.06–43.94) months vs 47.21 (21.23–50.77) months, respectively] (p=0.037). The median PFS was not reached in patients with maintenance treatment, in patients without maintenance treatment the median PFS was detected 23 (10-35.9) months (p=0.058). Conclusion: An induction regimen should be well chosen to ensure a deep and prolonged response, and maintenance treatment should be preferred in suitable patients to maintain response in transplant-ineligible patients.